A Miniature Forward-imaging B-scan Optical Coherence Tomography Probe to Guide Real-time Laser Ablation - Li, Zhuoyan (2014)
BACKGROUND AND OBJECTIVE: Investigations have shown that pulsed lasers tuned to 6.1 μm in wavelength are capable of ablating ocular and neural tissue with minimal collateral damage. This study investigated whether a miniature B-scan forward-imaging optical coherence tomography (OCT) probe can be combined with the laser to provide real-time visual feedback during laser incisions. STUDY DESIGN/METHODS AND MATERIALS: A miniature 25-gauge B-scan forward-imaging OCT probe was developed and combined with a 250 μm hollow-glass waveguide to permit delivery of 6.1 μm laser energy. A gelatin mixture and both porcine corneal and retinal tissues were simultaneously imaged and lased (6.1 μm, 10 Hz, 0.4-0.7 mJ) through air. The ablation studies were observed and recorded in real time. The crater dimensions were measured using OCT imaging software (Bioptigen, Durham, NC). Histological analysis was performed on the ocular tissues. RESULTS: The combined miniature forward-imaging OCT and mid-infrared laser-delivery probe successfully imaged real-time tissue ablation in gelatin, corneal tissue, and retinal tissue. Application of a constant number of 60 pulses at 0.5 mJ/pulse to the gelatin resulted in a mean crater depth of 123 ± 15 μm. For the corneal tissue, there was a significant correlation between the number of pulses used and depth of the lased hole (Pearson correlation coefficient = 0.82; P = 0.0002). Histological analysis of the cornea and retina tissues showed discrete holes with minimal thermal damage. CONCLUSIONS: A combined miniature OCT and laser -delivery probe can monitor real-time tissue laser ablation. With additional testing and improvements, this novel instrument has the future possibility of effectively guiding surgeries by simultaneously imaging and ablating tissue.